PENGARUH INTENSITAS PENDIDIKAN AGAMA ISLAM DI LINGKUNGAN KELUARGA DENGAN EQ PESERTA DIDIK - Betti Megawati; Fauzi Ahmad Syawaluddin; Syahputra Siregar (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2021)
This study aims to see the effect of PAI intensity in the family with the Emotional Quotient (EQ) of students. The research took place at MTs Negeri 2 Rantauprapat. The research used a survey method. Using regression analysis in measuring the effect of changing existing variables. The number of samples was 140 students. There is a positive relationship between PAI intensity in the family environment and the Emotional Quotient (EQ). It can be seen from the correlation coefficient value, it is known that rxy = 0.427> rt (0.05) = 0.312 then the significant level of rxy = 0.427> rt (0.01) = 0.403 means significant. There is a positive relationship between the intensity of PAI in the family environment with the Emotional Quotient (EQ) of students, through the Freg test, the value is 8.495, then the results are consulted with the table Ft (0.05) = 4.10 and Ft (0.01 ) = 7.35. So that Freg = 8.495> Ft (0.05) = 4.10 then Ft (0.01) = 7.35 so that the hypothesis that there is a positive relationship between the intensity of PAI in the family environment with the Emotional Quotient (EQ) Charter is acceptable